Fresno County Bar Association Luncheon re "Volunteers in Parole" Program - Watkins, Howard::::::::: (1989)
Fresno County Bar Association President-Elect bb, Volunteers in Parole Executive Director John Hix, Fresno-VIP Administrative Assistant Sally Keenan and Fresno County Bar Association President G. Dana French